1991
DOI: 10.1002/ssu.2980070106
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and pitfalls in the treatment of parotid tumors

Abstract: Any swelling near the ear is best considered a parotid neoplasm until proved otherwise. The diagnosis is primarily based on the clinical examination. Imaging studies are best reserved for patients who present with palate or tonsil swellings, which must be distinguished from parapharyngeal or minor salivary gland tumors. Almost all benign, and most malignant parotid tumors can be resected with preservation of the facial nerve. Aspiration biopsy can add useful information, but is not essential for treatment plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…Differences in the choice of treatment or referral pattern of patients may have influenced the results in the 34-year study period, but we were not able to detect any differences in survival and recurrence rates over the years. In contrast, Spiro et al (3,18,25) reported that patients diagnosed before 1966 had a shorter period of survival than those treated after 1966, and explained this as being due to a higher proportion of low-malignant histological types and more adequate surgical procedures after 1966. Treatment was analysed with all known confounding factors (i.e., histology, and clinical stage and nodes) in the present study, but we cannot exclude that the effect of treatment may be due to some unknown factor of patient selection.…”
Section: Tablementioning
confidence: 81%
“…Differences in the choice of treatment or referral pattern of patients may have influenced the results in the 34-year study period, but we were not able to detect any differences in survival and recurrence rates over the years. In contrast, Spiro et al (3,18,25) reported that patients diagnosed before 1966 had a shorter period of survival than those treated after 1966, and explained this as being due to a higher proportion of low-malignant histological types and more adequate surgical procedures after 1966. Treatment was analysed with all known confounding factors (i.e., histology, and clinical stage and nodes) in the present study, but we cannot exclude that the effect of treatment may be due to some unknown factor of patient selection.…”
Section: Tablementioning
confidence: 81%
“…Bilateral cases are mostly heritable though often without a family history (1) as was with our patient, but whether these factors determine metastasis to salivary glands is not clear. Parotid gland malignancies are itself fairly uncommon accounting for only 3-6% of head and neck carcinomas and 0.3% of all malignancies (11). Metastatic spread to the major salivary glands may take place by lymphatic spread, hematogenous dissemination or by direct extension with parotids being the primary site of lympho-hematogenous spread as it contains around 20 to 30 lymph nodes and a dense network of lymphatic channels (12).…”
Section: Discussionmentioning
confidence: 99%
“…All of the patients had a palpable mass on presentation and 19 of the patients were asymptomatic. Associated symptoms included painful or tender masses (7), pulsatile mass (2), bruit over mass (1), tinnitus (1), ipsilateral facial weakness (1), and numbness of the ipsilateral commissure of the lip (1).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Malignancies of the parotid gland are relatively uncommon, accounting for only 3-6% of all head and neck cancers and 0.3% of all cancers [1]. Approximately 30% of parotid tumors are malignant and most represent primary salivary gland tumors.…”
Section: Introductionmentioning
confidence: 99%